Using Live Imaging and FUCCI Embryonic Stem Cells to Rank DevTox Risks: Adverse Growth Effects of PFOA Compared With DEP Are 26 Times Faster, 1,000 Times More Sensitive, and 13 Times Greater in Magnitude - Abdulhasan, Mohammed; Ruden, Ximena; You, Yuan; Harris, Sean M.; Ruden, Douglas M.; Awonuga, Awoniyi O.; Alvero, Ayesha; Puscheck, Elizabeth E.; Rappolee, Daniel A. (Frontiers in Toxicology, 2021)
Fluorescence-ubiquitinated cell cycle indicator (FUCCI) embryonic stem cells (ESC), which fluoresce green during the S-G2-M phases, generate an S-shaped curve for accumulation of cells during normal stemness (NS) culture with leukemia-inhibitory factor (LIF). Since it was hypothesized that a culture of ESC were heterogeneous in the cell cycle, it was expected that increased S-G2-M-phases of the cell cycle would make an S-shaped curve parallel to the accumulation curve. Unexpectedly, it was observed that the fraction of FUCCI ESC in green decrease over time to a nadir at ~24hr after the previous feeding and then rapidly enter S-G2-M-phases after media change. Perfluoro-octanoic acid (PFOA) and diethyl phthalate (DEP) were used as examples of members of the per- and polyfluoroalkyl substances (PFAS) and phthalate families of chemicals, respectively. Two adverse outcomes were used to compare dose- and time-dependent effects of PFOA and DEP. The first was cell accumulation assay by time lapse confluence measurements, largely at Tfinal/T74hr. The second was by quantifying suppression of green Fed/unfed peak. By speed, PFOA is 26 times faster than DEP for producing a time-dependent LOAEL dose at 100uM (i.e., 2hr for PFOA, 52hr for DEP). PFOA has 1000-fold more sensitive LOAEL doses than DEP for suppressing ESC accumulation (confluence) at day 3 and day 2. There were two means to compare the magnitude of growth suppression of PFOA and DEP. For suppression of accumulation of cells measured by confluence at Tfinal/T74hr, there was a 45fold suppression at highest dose of PFOA>highest dose DEP. For suppression of entry into cell cycle after G1-phase by stress on day 1 and 2, there is 2.5fold more suppression by PFOA than DEP. The data presented here suggest that FUCCI ESC can assay suppression of accumulated growth or predict suppression of future growth by suppression of Fed/unfed green fluorescence peak and that PFOA adverse effects are faster and larger and occur at more sensitive lower doses than DEP.